2024
DOI: 10.1001/jama.2024.1447
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-Controlled Transient Elastography Scores to Predict Liver-Related Events in Steatotic Liver Disease

Huapeng Lin,
Hye Won Lee,
Terry Cheuk-Fung Yip
et al.

Abstract: ImportanceMetabolic dysfunction–associated steatotic liver disease (MASLD) is currently the most common chronic liver disease worldwide. It is important to develop noninvasive tests to assess the disease severity and prognosis.ObjectiveTo study the prognostic implications of baseline levels and dynamic changes of the vibration-controlled transient elastography (VCTE)–based scores developed for the diagnosis of advanced fibrosis (Agile 3+) and cirrhosis (Agile 4) in patients with MASLD.Design, Setting, and Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Similarly, baseline LSM was an independent risk factor for developing HCC, hepatic decompensation and liver-related death in individuals with advanced MASLD-related fibrosis/ compensated cirrhosis [189]. In longitudinal studies with serial VCTE measurements, changes in LSM (20% increase, stable, 20% decrease) correlated with the risk of liver-related events (including HCC) and liver-related death [176,189]. In a retrospective analysis in persons with advanced fibrosis included in clinical trials, an LSM cut-off of ≥16.6 kPa (HR 3.99, 95% CI 2.6-5.98) and a ≥5.5 kPa increase (and ≥20%; HR 1.98, 95% CI 1.20-3.26) predicted the development of cirrhosis, whereas LSM ≥30.7 kPa predicted liver-related events (HR 10.13, 4.38-23.41) [190].…”
Section: Recommendationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, baseline LSM was an independent risk factor for developing HCC, hepatic decompensation and liver-related death in individuals with advanced MASLD-related fibrosis/ compensated cirrhosis [189]. In longitudinal studies with serial VCTE measurements, changes in LSM (20% increase, stable, 20% decrease) correlated with the risk of liver-related events (including HCC) and liver-related death [176,189]. In a retrospective analysis in persons with advanced fibrosis included in clinical trials, an LSM cut-off of ≥16.6 kPa (HR 3.99, 95% CI 2.6-5.98) and a ≥5.5 kPa increase (and ≥20%; HR 1.98, 95% CI 1.20-3.26) predicted the development of cirrhosis, whereas LSM ≥30.7 kPa predicted liver-related events (HR 10.13, 4.38-23.41) [190].…”
Section: Recommendationsmentioning
confidence: 91%
“…Evidence also exists for the ability of elastography techniques such as LSM by transient elastography to predict outcomes in MASLD (Table 6]. Several observational studies showed that LSM had good accuracy for liver-related events, liver-related and overall mortality [176,183,188]. Similarly, baseline LSM was an independent risk factor for developing HCC, hepatic decompensation and liver-related death in individuals with advanced MASLD-related fibrosis/ compensated cirrhosis [189].…”
Section: Recommendationsmentioning
confidence: 99%
“…The use of the Agile-3+ score that is more closely and dynamically associated with an increased risk of liverrelated events might represent an alternative. 52 The availability of resmetirom in real life opens another key question: how and when to define the response to the treatment? Data from clinical trials showed that both a 3-month ≥30% improvement in MRI-PDFF assessed hepatic fat content and ≥ 17 IU reduction of serum ALT levels from baseline can identify histological responders.…”
Section: Clinic Al Implementationmentioning
confidence: 99%
“…7,9 In addition, vibration-controlled transient elastography-based scores are highly accurate in predicting liver-related events in patients with metabolic dysfunction-associated steatotic liver disease. 11 The use of MRI-PDFF and vibration-controlled transient elastography as valid evaluation criteria in clinical practice needs to be assessed in larger clinical trials.…”
Section: Challenges Of Thr-β Agonist In Clinical Practicementioning
confidence: 99%